Depression In Type 2 Diabetes Mellitus : A Cross-Sectional Study In Tertiary Care Teaching Hospital In India - Varma, P.; Kant, R.; Mishra, P.P. (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Introduction: In our country, number of patients of diabetes is increasing every year, so of depression. The emotional consequences of diabetes have been scrutinized in a number of studies and varying results about the association of depression with type 2 diabetes mellitus have been found. While depression may contribute to poor diabetes-related outcomes, diabetes and its complications may also contribute to poor depression outcomes. Both conditions may have common underlying biological and behavioural mechanisms, such as genetic susceptibility and common pathophysiological mechanism. AIM-To assess the prevalence and the factors associated with depression among the patients with type II diabetes mellitus.Materials and Methods: Single centre, descriptive, cross-sectional study conducted in tertiary care teaching hospital in India for a period of 8 months. 586 type II diabetes patients aged between 30 and 70 years were included. Patients taking mood elevator drugs, suffering from mental illness, gestational diabetes and type 1 diabetes were excluded from the study. Physicians Health Questionnare-9 (PHQ-9) with a score of ≥5 was used to make the diagnosis of depression.Results: Prevalence of depression among the diabetic patients found to be 49.48%. Many factors have been found to be associated with increased prevalence of depression among diabetic patients such as age, female gender, house wife, high BMI, diabetes duration, diabetes related complications, comorbid conditions and poor glycaemic control with poor follow-up.Conclusion: By managing both depression and diabetes concurrently, better outcome in patients and increase in overall quality of life can be achieved. Early detection and treatment of depression by effectively screening all diabetic patients for depression would help to bring down the severity of depression among these patients.Jour of Diab and Endo Assoc of Nepal 2018; 2 (1): 24-28